Assessment of HIV Knowledge in Correctional Facility Health Care Workers: A Pilot Study of an Educational Intervention. (July 2016) - Hoang, Holly L.; Khan, Muhammad Naeem; Berger, Sara; Moreau, Danusia; Nickel, Pamela; Woods, Dan; Jaipaul, Joy; Pyne, Diane; Moreland, Barbara; Singh, Ameeta; Ahmed, Rabia
HIV rates are disproportionately higher in the incarcerated compared to the general population. Unfortunately, HIV sero-positive inmates report perceived discrimination and missed antiretroviral doses. Correctional facility nursing competency in HIV management may mitigate these concerns. Using validated knowledge instruments, the authors measured baseline HIV knowledge in correctional facility nurses from 3 correctional facilities in Alberta, Canada, and quantified changes after a targeted educational workshop. Basic HIV knowledge increased significantly, whereas perceived need for further HIV education significantly decreased postintervention. This study demonstrates that correctional facility nurses may not receive ideal HIV education during employment and that targeted HIV workshops can significantly increase knowledge and confidence when caring for affected individuals.